Racialized Economic Segregation and Disparities in Non-Small Cell Lung Cancer Care and OutcomesTake-home Points - Pratibha Shrestha, MPH, PhD; Min Lian, MD, PhD; James Struthers, BA; Oumarou Nabi, PhD; Bayu B. Bekele, MPH, PhD; Benjamin Kozower, MD; Maria Baggstrom, MD; Ying Liu, MD, PhD (CHEST Pulmonary)
Background: Little is known about the impact of residential segregation on early detection, treatment, and prognosis of non-small cell lung cancer (NSCLC), a predominant type of lung cancers. Research Question: Does racialized economic segregation play a role in NSCLC treatment and outcomes and contribute to racial disparities? Study Design and Methods: This study included non-Hispanic White (NHW) and non-Hispanic Black (NHB) patients with NSCLC diagnosed between 2007 and 2015 and identified from the Surveillance, Epidemiology, and End Results data set. County-level racialized economic segregation was estimated by using the Index of Concentration at the Extremes (ICE). Multilevel logistic regression and multilevel Cox regression accounting for county-level clustering were used to estimate ORs for late-stage diagnosis and treatment underutilization, and hazard ratios (HRs) were used for mortality. Results: Of 203,441 patients, 85.8% were NHW, and 14.2% were NHB. Compared with patients living in the counties with the highest concentration of high-income NHW households (lowest ICE quintile), patients living in the counties with the highest concentration of low-income NHB households (highest ICE quintile) had higher risks of late-stage diagnosis (OR, 1.09; 95% CI, 1.02-1.16; Ptrend < .001), underutilization of guideline-recommended treatment (OR, 1.28; 95% CI, 1.16-1.41; Ptrend < .0001), lung cancer-specific mortality (HR, 1.10; 95% CI, 1.07-1.14; Ptrend < .0001), and overall mortality (HR, 1.12; 95% CI, 1.09-1.16; Ptrend < .0001). The association between segregation and treatment underutilization was stronger in NHW patients than in NHB patients (Pinteraction = .02). There was no significant difference in the segregation-related risk of late-stage diagnosis, lung cancer-specific mortality, or overall mortality between NHW and NHB patients. Interpretation: Living in segregated, low-income counties with predominately NHB residents has adverse impacts on early detection, treatment, and outcomes of NSCLC. However, residential segregation did not explain the excess risks of NSCLC care underutilization and mortality in NHB patients compared with NHW patients.